The Effect of PHC Digital Innovations and Performance-Based Incentives on Uptake of Maternal and Child Health Services in Selected Pilot Sites in Kenya - Matiang'i, Micah; Ngunju, Priscilla Wanjiru; Hetyey, Aranka; Sluijs, Jose; Smet, Eefje; Harkx, Romy; Odhiambo, Paul Odhiambo (Open Journal of Clinical Diagnostics, 2024)
Abstract Background: While global efforts have led to a decline in maternal and neo natal mortality, Sub-Saharan Africa continues to face disproportionately high rates, remaining far above the Sustainable Development Goal (SDG) targets. In Kenya, as the 2030 SDG deadline approaches, the gap in maternal, neonatal, and child health servicesremainssignificant. Addressing these challengesis crit ical to improving Maternal, Neonatal, and Child Health (MNCH) outcomes. Objective: This study explores how integration of digital health innovations into the MNCH chain ofservice delivery affectsthe quality of MNCH care within the selected PHC settingsinKajiado,Kisii and MigoriCountiesinKenya. Meth odology: This Quasi-experimentalstudywas conducted 1-year post-intervention targeting a total of 482 pregnant women from intervention and control sites in Kisii, Kajiado and Migori Counties, Kenya. Data was analysed using Chi Square test comparing frequencies between intervention and control groups when both variables are categorical. Results: Pre-intervention data revealed an increase in first ANC coverage within first trimester, from 167 to 278 post intervention (p < 0.001). Fourth ANC coverage rose from 984 to 1177 women while Linda mama social health insurance registrations increased from 1008 to 1135. At the intervention sites, 938 pregnant women got screened by mid wives using portable mobile Obstetric Point-of-Care Ultrasound (OPOCUS) technology compared to the 27 cases that accessed ultrasound services in the noncontiguous control sites. The pilot sites midwives earned themselves an incentive income totaling Ksh 400,000 while the Community Health Promot ers (CHPs) who created demand for OPOCUS earned an incentive income to taling Ksh 327,195 from their IGAs that were project supported. There was significant increase in mobile health application usage and e-resources access for health information in the intervention group (p < 0.001). Nutritional be haviors also improved, with higher fruit and vegetable consumption in the in tervention group (p < 0.001 for fruits, p = 0.048 for vegetables) and lower meat consumption (p = 0.014). Although no significant differences were found in BCG and OPV birth dose coverage, vaccination dropout rates were notably lower in the intervention group (17%) compared to the control group (48%). Qualitative data indicated that mobile app-based ANC services enrolment and health education had enhanced pregnant women’s confidence and utilization of services and improved adherence to referrals. Conclusion: The success of dig ital health interventions in improving health-seeking behaviour, knowledge, and service uptake highlights the potential of such innovations to strengthen health systems and achieve universal health coverage. We recommend the in tervention for a scale-up in other PHC settings in Kenya.
Copyright © 2024 by author(s) and Scientific Research Publishing Inc. This work is licensed under the Creative Commons Attribution International License (CC BY 4.0).
Keywords: Maternal and Child Health; Digital Health Innovations; Performance-Based Incentives; Antenatal Care; Health Service Utilization